LAB da longevidade: um laboratório em realidade virtual para ensino na prática de cuidadores de pessoas idosas - Alalan, Carine Pereira (Universidade do Vale do Rio dos Sinos, 2025)
The dissertation aimed to analyze the challenges and possibilities that are present in the development of a virtual reality laboratory in a course for elderly caregivers in a private technical education institution focused on the health area. In this study, data triangulation was considered, through document analysis (document analysis), technical visit to a reference space for elderly care (observational analysis) and semi-structured interviews (regarding the procedure). The results were organized with categorization, highlighting the profile of the participants, the challenges in the caregiver's performance, the challenges in integrating technologies in the Elderly Care course, the benefits of implementing a virtual reality laboratory and the elements and themes to be used in the laboratory. The intervention proposal consists of a descriptive project for the implementation of the Longevity LAB, using as a basis the Learning Object Request document used in the institution where the research was conducted. This model was chosen so that the project can be absorbed by the institution and implemented based on the work presented, but nothing prevents it from being explored by other institutions that believe in this proposal. In conclusion, the contributions of this research highlight the importance of integrating technologies, such as virtual reality, into the training process for caregivers of elderly people. The findings not only help to understand the benefits of this technology, but also pave the way for the implementation of an innovative, inclusive and accessible teaching model.
Keywords: Cuidador de pessoa idosa; Realidade virtual; Tecnologia educacional; Ensino e aprendizagem; Elderly caregiver; Virtual reality; Educational technology; Teaching and learning; ACCNPQ::Ciências Humanas::Educação